The 2003 Rugby World Cup: Player Image as Intellectual Property - Sadler, Pauline; Yorke, Cameron (Curtin University of Technology, 2003)
International sporting events such as the Olympic Games,World Cup Soccer, World Cup Cricket and the Rugby Union World Cup are big business. They present an international showcase for particular sports and individual participants. However an issue that is often managed poorly by the administrators and organisers is the intellectual property rights of the participants. This is particularly evident where the administrators and organisers attempt to prevent ambush marketing through the use of player image. This paper examines the use of player image in the context of the 2003 Rugby World Cup, and, in particular, the terms of the contentious 'participation agreement' that each player had to sign before being able to compete. The provision of some background information about the Rugby World Cup,leads to discussion of ambush marketing in sport is discussed, and examines the legal rights of players to make economic use of their own persona, or image, as they choose, a feature known as 'character merchandising'. A discussion of the effect of 'restraint of trade' clauses in employment contracts leads to a series of recommendations. Discuss some recommended strategies that aim to satisfy all parties and prevent the use of player image as a method of ambush marketing.